2020
DOI: 10.1088/2053-1591/abb426
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of wear and erosion-corrosion resistance of Inconel 718 alloy by liquid nitriding

Abstract: Inconel 718 alloy is often used for the oil and gas industry, which usually failed due to the erosion-corrosion of multi-phase flow. In this study, we expect to enhance the wear and erosion-corrosion resistance of Inconel 718 alloy by liquid nitriding and a high-hardness nitrided layer with the thickness of about 9.5 μm on the surface of Inconel 718 alloy was formed by liquid nitriding. Wear and erosion-corrosion tests were performed on untreated and nitrided Inconel 718 alloys. Results show that abrasive wear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 45 publications
7
13
0
Order By: Relevance
“…It may prove the higher effectiveness of the plasma nitriding over cathode one. Similar response was reported by Xue et al [26].…”
Section: Effect Of the Nitriding Technique On Oxidation And Mechanical Response Of Inconel 740h Alloysupporting
confidence: 91%
See 2 more Smart Citations
“…It may prove the higher effectiveness of the plasma nitriding over cathode one. Similar response was reported by Xue et al [26].…”
Section: Effect Of the Nitriding Technique On Oxidation And Mechanical Response Of Inconel 740h Alloysupporting
confidence: 91%
“…The positive effect of nitriding on the corrosion resistance of nickel-based alloys was also indicated in the literature. Xue et al [26] reported a significant improvement in the erosion-corrosion resistance (almost 80.3%) if compared to the as-received Inconel 718. Such improvement was associated to the chromium nitride found on the surface.…”
Section: Effect Of the Nitriding Technique On Oxidation And Mechanical Response Of Inconel 740h Alloymentioning
confidence: 97%
See 1 more Smart Citation
“…Xue et al showed that the nitrided layer achieves a hardness that is several times higher than that of Inconel (1800 HV0.01 and about 400 HV, respectively). Moreover, the results presented by Authors, prove that the nitrided layer strongly improves abrasive wear resistance [ 57 ]. Based on that, it is expected that the oxide layer formed in this study might have a beneficial effect on increased hardness and wear resistance, which is promising course for future studies.…”
Section: Resultsmentioning
confidence: 99%
“…The ceramic layer on the surface of Inconel 718 can have a very beneficial effect on hardness and wear resistance due to its properties. An example can be the nitrided layer on the IN718 surface [57,58]. Xue et al showed that the nitrided layer achieves a hardness The formation of the oxide layer might have significant influence on the mechanical as well as the tribological performance due to the current knowledge.…”
Section: Oxidation Layermentioning
confidence: 99%